Gamification in vocational education: a comparative analysis of existing research frontiers - Omarova, M.K.; Geli§li, Y. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2025)
The modern transformation of education requires teachers to modernize outdated motivational schemes and apply new technologies of interaction with the modern generation of students. One of the innovations that technology has brought to the educational environment is gamification. In the article is current research and publications on gamification in education, including vocational education analyzed. Gamification in vocational education is a relatively new field of research. In recent years, scientific achievements in the field of gamification in education have grown rapidly. The growing number of publications on the application of gamification in education remains insufficient in terms of the development of scientific and methodological approaches to the use of gamification tools in the process of professional education, its use by teachers in the development of courses. In the article, research on the application of gamification in vocational education over the past five years was analyzed by the authors from several aspects. In the conclusion, the results of the conducted research analysis were shared by authors. The need to study the application of gamification in vocational education in Kazakhstan and to consider the possibility of applying gamification tools as an integral part of digital educational platforms of universities was noted by the authors.
Кэсштж бш1м беру геймификациясы: зерттеудщ KOлданыстаFы фронтирлерше салыстырмалы талдау
Геймификация профессионального образования: сравнительный анализ существующих фронтиров исследования
Keywords: gamification; gamification tools; game technologies; education; vocational education; frontier; publication; learning motivation